FRI0225 Use of abatacept in patients with rheumatoid arthritis from the rhumadata® database: experience as first or second line agent compared with adalimumab and etanercept. (23rd January 2014) - Choquette, D.; Sauvageau, D.; Haraoui, B.; Pelletier, J.-P.; Raynauld, J.-P.; Villeneuve, E.; Coupal, L.
Abstract : Background: The order of use of biologic agents is still a question of debate. Phase III trial data in MTX-IR patients show very similar results across all biologic agents. No head to head study have yet been published. Prospective registries offer a unique opportunity to observe the effectiveness of these agents in a clinical setting. Objectives: To evaluate if patients with rheumatoid arthritis (RA) treated with abatacept after failure to either a first line agent (MTX-IR) or a second line anti-TNF agents (TNF-IR) have a different drug survival rate compare to adalimumab or etanercept similarly prescribed in Rhumadata database. A secondary objective is to explore the role of MTX coprescription. Methods: Data from patients with RA fulfilling the the ACR criteria and/or according to a rheumatologist diagnosis were extracted from the database from the 1 st of January 2007. Two cohorts were extracted. The first cohort consists of patients that had failed MTX and had started either adalimumab (ADA), Etanercept (ETA) or Abatacept (ABA). Subjects in the second RA cohort had failed a first anti-TNF agent and had started an alternative treatment with either ADA, ETA or ABA. RHUMADATA® is a clinical database/software used in daily clinical practice at the IRM. Results: 290 patients were extracted. 203 were included in the first cohort and 87 composed the second cohort. Baseline demographics for both cohorts included age, disease duration, HAQ, fatigue and pain evaluation, TJC, SWC, DAS 28 ESR and SDAI. No significant differences in baseline variables were observed between treatment groups (GLM). Statistical analysis was performed using SAS version 9.3. The 5 year retention rate of abatacept, adalimumab and etanercept post MTX failure are respectively 63%, 54% and 50% without significant statistical differences (Wilcoxon p=0.6779). In that cohort, patients taking MTX with their biologic agent (ABA, ADA or ETA) demonstrated a better drug survival rate than those taking monotherapy (60% vs 32%, Wicoxon p=0.0079). All biologics combined to DMARDS exibited similar survival profiles (ETA 62%, ABA 58%, ADA 50% at 5 years, Wilcoxon p=0.4681). However, patients having failed a first anti-TNF agent showed a better drug survival rate if treated with ABA compared to ADA or ETA. Respective retention rates at 5 years are: ABA 48%, ADA and ETA 31% (Wilcoxon p=0.0381). Conclusions: Abatacept, adalimumab and etanercept after MTX failure show similar 5-years retention rates. Combination with methotrexate improved the biologic agents survival rate at 5 years. Prescribing abatacept after a previous TNF agent failure seems to offer a more favorable alternative. References: Sequential use of biologic therapy in RA. Buch MH. Curr Opin Rheumatol 2010 May;22(3): 321-9Switching TNF-Alpha antagonists in RA: the experience of the Lorhen registry. Caporali R & al. Autoimmune Rev. 2010 Apr;9(6): 465-9Treatment options in patients with RA failing initial TNF inhibitor therapy: a critical review. Rubbert-Roth A, Finckh A. Arthritis Res Ther. 2009;11 Suppl 1:S1 Acknowledgements: The Rhumadata registry is supported by unrestricted grant from Abbott Canada, Amgen Canada, BMS Canada, Pfizer Canada, Roche Canada, UCB Canada Disclosure of Interest : None Declared